Cue-Induced Ethanol Seeking in Drosophila melanogaster Is Dose-Dependent - Nunez, Kavin M.; Azanchi, Reza; Kaun, Karla R. (Frontiers in Physiology, 2018)
Alcohol use disorder generates devastating social, medical and economic burdens, making it a major global health issue. The persistent nature of memories associated with intoxication experiences often induces cravings and triggers relapse in recovering individuals. Despite recent advances, the neural and molecular mechanisms underlying these memories are complex and not well understood. This makes progress in finding effective pharmacological targets challenging. The investigation of persistent alcohol-associated memories in the fruit fly, Drosophila melanogaster, presents a unique opportunity to gain a comprehensive understanding of the memories for ethanol reward at the level of genes, molecules, neurons and circuits. Here we characterize the dose-dependent nature of ethanol on the expression of memory for an intoxication experience. We report that the concentration of ethanol, number of ethanol exposures, length of ethanol exposures, and timing between ethanol exposures are critical in determining whether ethanol is perceived as aversive or appetitive, and in how long the memory for the intoxicating properties of ethanol last. Our study highlights that fruit flies display both acute and persistent memories for ethanol-conditioned odor cues, and that a combination of parameters that determine the intoxication state of the fly influence the seemingly complex retention and expression of memories associated with intoxication. Our thorough behavioral characterization provides the opportunity to interrogate the biological underpinnings of these observed preference differences in future studies.